A comprehensive study of potential Arthrospira platensis cultivated in various manure‐based media for biodiesel feedstock - Rachmawati Rusydi; Eva Ayuzar; Muliani Muliani; Saifuddin Saifuddin (Indonesian Journal of Biotechnology, 2024)
Arthrospira platensis has emerged as a promising biodiesel feedstock due to its rapid growth and substantial biomass. In efforts to reduce production costs, researchers have explored alternative media derived from livestock waste to modify conventional mediums for Arthrospira platensis cultivation. The experimental design of this research employed a Completely Randomized Design, with treatments comprising inorganic fertilizer (A), chicken manure (B), cow manure (C), and goat manure (D). The livestock manures were macerated for seven days before being utilized as A. platensis medium. The results revealed significant (p < 0.05) impacts of different media on peak growth values and biomass production, reaching 2.03 ± 0.06 g/L and 1.76 ± 0.05 g/ L, respectively for chicken manure. The highest peak lipid content was observed in A. platensis cultured in goat manure medium. This study recommends goat manure as the preferred medium for mass cultivation of A. platensis. Mass cultivation in goat manure medium yielded 1.53 kg of dried biomass, with a lipid content of 1.91% and a biodiesel yield of 1.65%. The predominant fatty acid in this biodiesel was heneicosane, constituting 26.4% of the total area.